DNA binding of ethyl 2-substituted aminothiazole-4-carboxylate analogues: A molecular modeling approach to predict their antitumor activity - Laila A. Abouzeid; Hussein I. El-Subbagh (SpringerOpen, 2015)
The synthesis and the antitumor potential of 2-substituted aminothiazole-4-carboxylate, structurally-related to the antitumor antibiotic netropsin (NT) were reported. However, the exact mode of action and SAR of these compounds remained undefined. Currently, an energy-based molecular modeling approach has been utilized to highlight the mode of interaction of these compounds with β-DNA and characterize the structural requirements of biologically active aminothiazoles. Employing netropsin (NT) as a template and nine different 2-aminothiazole analogues have been examined for their capacity to interact with the DNA structure based on the number and pattern of H-bonding, energy of binding, conformational changes of compounds due to docking, and the width change of DNA minor groove. Positive correlation (R2 = 0.94) was found between (Ebinding) of the used 2-aminothiazoles and their antitumor activity, thus substantiating the utility of this modeling approach in future design of similar compounds.